The Effect of Awareness on the Behavior of Advertisement on Social Network Basis for Cosmetic Products Line - Pham Van Tuan; Pham Sy Phuc; Tran Van Nguyen; Tran Thi Thu Trang; Dinh Tran Ngoc Huy; Hoang Thi Nga; Pham Thi Hong Nhung; Bui Thi Hong Chinh (Newinera Publisher, 2022)
The study examines the factors affecting the perception and interaction behavior with advertising cosmetic products. The authors used SPSS and Smart PLS software to conduct statistics and analyze survey results. The results of data analysis show that there are 5 factors that directly affect the perception of avoidance: Health concerns; Doubts about advertising intermediaries; Privacy concerns; Information value; Obstructing cognitive goals. The factor that directly affects Avoidant Behavior is Perception of avoidance, there are 5 factors that indirectly affect Avoidant Behavior: Health concerns; Doubts about advertising intermediaries; Privacy concerns; Information value; Obstructing cognitive goals. At the same time, the research also shows that negative experiences do not affect the impact process from Avoidant Perception to Avoidant Behavior. This study has important practical elements for businesses, managers and even social network users in reducing users' awareness and avoidance of advertising.